Eco-Friendly Innovations in Visual Arts: A Narrative Review - Nuristama, Ramadhina Ulfa; Effendi, Harris (Harmonia : Journal of Music and Arts, 2024)
This narrative review examines the intersections between visual arts and sustainability, focusing on eco-friendly materials, green practices in art education, and community engagement strategies. The study aims to synthesize how visual arts contribute to ecological awareness and sustainable practices, while identifying barriers and opportunities for greater impact. A systematic search was conducted across Scopus, Web of Science, and Google Scholar using keywords such as “sustainable visual arts,” “eco-friendly art materials,” and “green practices in art education.” Inclusion criteria emphasized peer-reviewed studies published between 2010 and 2024, covering both empirical and theoretical contributions. The results demonstrate that recycled and bio-based materials significantly reduce environmental footprints while inspiring innovative creative practices. Education emerges as a central driver, with sustainability-focused curricula preparing future artists to adopt eco-conscious methods. Community-based art projects further illustrate how participatory practices democratize sustainability discourse and enhance public engagement. Comparative insights reveal disparities between developed and developing countries, shaped by economic resources, institutional support, and policy frameworks. The discussion emphasizes the need for stronger policies, financial support, and interdisciplinary collaborations to overcome systemic barriers. While current literature has made significant strides, gaps remain in cross-cultural analysis and in understanding the behavioral impact of sustainable art on audiences. The findings underscore the importance of visual arts as both aesthetic expression and transformative agent, with urgent implications for policy, education, and future research.